Suppressing Local Dendrite Hotspots via Current Density Redistribution Using a Superlithiophilic Membrane for Stable Lithium Metal Anode. Issue 12 (17th February 2023) - Hu, Yifan; Li, Zichuang; Wang, Zongpeng; Wang, Xunlu; Chen, Wei; Wang, Jiacheng; Zhong, Wenwu; Ma, Ruguang
Abstract: Li metal anode is considered as one of the most desirable candidates for next‐generation battery due to its lowest electrochemical potential and high theoretical capacity. However, undesirable dendrite growth severely exacerbates the interfacial stability, thus damaging battery performance and bringing safety concerns. Here, an efficient strategy is proposed to stabilize Li metal anode by digesting dendrites sprout using a 3D flexible superlithiophilic membrane consisting of poly(vinylidene fluoride) (PVDF) and ZnCl2 composite nanofibers (PZEM) as a protective layer. Both the experimental studies and theoretical calculations show the origin of superlithiophilicity ascribed to a strong interaction between ZnCl2 and PVDF to form the ZnF bonds. The multifield physics calculation implies effective removal of local dendrite hotspots by PZEM via a more homogeneous Li + flux. The PZEM‐covered Li anode (PZEM@Li) exhibits superior Li deposition/stripping performance in a symmetric cell over 1100 cycles at a high current density of 5 mA cm −2 . When paired with LiFePO4 (LFP), PZEM@Li|LFP full cell remains stable over 1000 cycles at 2 C with a degradation rate of 0.0083% per cycle. This work offers a new route for efficient protection of Li metal anode for practical applications. Abstract : Digesting dendrites for stable Li‐metal anode is successfully realized by using a flexible superlithiophilic poly(vinylidene fluoride) and ZnCl2 electrospinning membrane as an interfacial protective layer.